After the disaster - Hart, Keith (Anthropology Today, 2008)
Naomi Klein's The Shock Doctrine offers a weak analysis of ‘neoliberalism’ linked to a defeatist ideology. If we wish to move beyond the global economic crisis, we should borrow ideas from Mauss, Polanyi and Keynes; but the political level for an appropriate response is not obvious.
Anthropology
Keywords: KLEIN; Naomi; neoliberalism

Karl Polanyi's Legacy - Hart, Keith (Development and Change, 2008)
Click on the article title to read more.
Anthropology; Development Studies
Keywords: biography

Anthropology in the financial crisis - Hart, Keith; Ortiz, Horacio (Anthropology Today, 2008)
This editorial considers the opportunities opened up for anthropologists by the financial crisis of 2008. The chief of these is the exposure of cracks in the intellectual hegemony of free-market economics which contributed to an unnecessarily defensive posture on the part of most anthropologists during the period of neoliberal globalization. The authors claim that anthropology can bridge the gap between everyday life and the world at large by combining the study of ideas and social actions. We draw on Ortiz's research among financial professionals to show how working practices informed by economic liberalism can have extremely unequal consequences for the global distribution of resources. The perspectives of Mauss and Polanyi on political economy can help us to make sense of the current situation and to recommend a path forward beyond market fundamentalism. Their general ideas lend power to the concrete findings of field research. The mask of neoliberal ideology has been ripped from the politics of world economy. Anthropology's highest mission is to start from where people are and go with them wherever they take you. What better time to follow this imperative than when the model the world has been compelled to live by for three decades is in such disarray?
Anthropology
Keywords: finance; financial crisis